Analysis of parental saving on childrens tertiary education - Tan, Xiao Fang (2021)
The purpose of this study is to analyze parental savings for childrens tertiary education.This study used a questionnaire set as the research instrument and purposive samplingmethod had been adopted for data collection purposes. A total of 392 respondents; which werecomprised of parents with children at tertiary education level participated in thisstudy. Data were analyzed through mean, frequency, percentage, multiple regressionanalysis tests and were processed by using SPSS software version 23. The resultsshowed, there is no significant difference between number of parents who make savings and thenumber of parents who do not make savings for their childrens tertiary education. In addition, ownsavings accounts were identified as the most popular medium of savings among the parents. Thefindings of multiple regression analysis showed that; income (= 0.179, p = 0.001), peoplesurrounding ( = 0.392, p = 0.000), expectation ( = 0.364, p = 0.000) and institutions ( =0.146, p = 0.014) factors were positively and significantly related to parental saving.Meanwhile, only awareness ( = 0.047, p = 0.328) factor was found to be insignificant. Inconclusion, all parties should work together to increase public awareness in recognizing theimportance of making savings as early as possible to ensure sufficient savings to cover the cost ofchildrens tertiary education. Bank and non- bank institutions can offer attractive and affordableschemes to enable parents to make loans according to their ability. The findings of thisstudy may provide successful implications to parental awareness on the importance of financialplanning and adequatesavings to fund their children tertiary education.